Metode Istinbath Hukum Nafkah Iddah Talak Bain Menurut Syafi'iyyah - Tiyan Hasanah (Nizham Jurnal Studi Keislaman, 2020)
Iddah is one of the obligations of a wife who is divorced by her husband. During iddah, the wife has the right to get a place to live and provide a living, that is what applies to talak raj'i and not to a wife who is divorced ba`in. This research is a library research. Nafkah Iddah the details of which are not explicitly explained in the Al-Qur'an and Hadith. This has led to differences of opinion among the schools of thought. Shafi`iyyah uses mafhum mukhalafah as an istinbaṭh method in understanding Surah ath-Talaq Verse 6 and uses the ahad Hadith from Fatimah bint Qais as the basis for the absence of iddah talaq bain for wives who are not pregnant. The use of mafhum mukhalafah by Shafi`iyyah affects the rule of law. According to Syafi`iyyah, pregnancy is a requirement or qayid for the obligatory support for the wife who has been bullied, which means that if there is no pregnancy, it is not obligatory to provide for the wife who is wronged.